2021
DOI: 10.3390/microorganisms9061286
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Triazole Thiol Irreversibly Inactivates Metastable HIV-1 Env by Accessing Conformational Triggers Intrinsic to Virus–Cell Entry

Abstract: KR13, a peptide triazole thiol previously established to inhibit HIV-1 infection and cause virus lysis, was evaluated by flow cytometry against JRFL Env-presenting cells to characterize induced Env and membrane transformations leading to irreversible inactivation. Transiently transfected HEK293T cells were preloaded with calcein dye, treated with KR13 or its thiol-blocked analogue KR13b, fixed, and stained for gp120 (35O22), MPER (10E8), 6-helix-bundle (NC-1), immunodominant loop (50-69), and fusion peptide (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 82 publications
(154 reference statements)
0
3
0
Order By: Relevance
“…Detected leakage was limited and dose-dependent (Supplemental Figure S4). Of note, in previous studies, where HIV-1 lysis was observed, p24 release occurred as an apparent result of disturbing the metastable structure of the HIV-1 Env spike, and causing conformational rearrangement and irreversible inactivation of spike before target cell encounter. We, therefore, explored this latter possibility for SARS-CoV-2 by examining the viruses after stringent washouts following lectin exposure, before target cell infection. Indeed, we observed that CV-N-treatment irreversibly inactivates SARS-CoV-2 pseudovirus, with an IC 50 of 242.2 ± 191.6 nM (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Detected leakage was limited and dose-dependent (Supplemental Figure S4). Of note, in previous studies, where HIV-1 lysis was observed, p24 release occurred as an apparent result of disturbing the metastable structure of the HIV-1 Env spike, and causing conformational rearrangement and irreversible inactivation of spike before target cell encounter. We, therefore, explored this latter possibility for SARS-CoV-2 by examining the viruses after stringent washouts following lectin exposure, before target cell infection. Indeed, we observed that CV-N-treatment irreversibly inactivates SARS-CoV-2 pseudovirus, with an IC 50 of 242.2 ± 191.6 nM (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Detected leakage was limited and dose-dependent (Supplemental Figure S4). Of note, in previous studies where HIV-1 lysis was observed, p24 release occurred as an apparent result of disturbing the metastable structure of the HIV-1 Env spike, and causing conformational rearrangement and irreversible inactivation of spike before target cell encounter (18)(19)(20). We therefore explored this latter possibility for SARS-CoV-2 by examining the viruses after stringent washouts following lectin exposure, before target cell infection.…”
Section: Cv-n Treatment Irreversibly Inactivates Sars-cov-2 Virus Par...mentioning
confidence: 99%
“…Macrocyclic peptide triazoles (cPTs) have been devised with molecular weights of less than 1000 Da (comparable to small molecules), protease resistance, and greatly increased serum half-life [12,13]. Furthermore, thiol functionalization of linear and cyclic PTs affords a subclass of variant PTs that cause further inactivation effects by virus membrane poration [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%